Synthesis of nanostructure active pharmaceutical ingredients for isoniazid and griseofulvin by cryogenic technology / Layth Abdulateef Hashim - Layth Abdulateef, Hashim (2011)
One of the major challenges in the pharmaceutical industries is to improve the physicochemical properties of newly discovered Active Pharmaceutical Ingredients (API). It is reported that 40% of the newly developed APIs are bioavailability limited, which means the API are not released at a desirable dissolution rate. The limitations are mainly due to low physicochemical properties such as solubility, dissolution rate and permeability. Improving physicochemical properties of APIs can be achieved through control of particle size distributions during production with the introduction of water-soluble polymers and/or surfactants, which act as additives to prevent particle agglomeration and crystal growth. Venturing into the nano-particle world by producing APIs at nano-scale through nano-particle formation processes are expected to enhance physicochemical properties of APIs. On the other hand, cryogenic and nucleation technologies are promising process that creates highly porous nano-structured particles compared to conventional process such as wet milling and high pressure homogenization which normally lead to degradation in API activities. This study consists of three main steps. Firstly, cryogenic surface was designed and fabricated using liquid nitrogen as a refrigeration media. The surface temperature range from -110°C to -90°C and the thermal conductivity of the surface made of stainless steel is 16 W/m.K. The procedure consists of dropping of solution from a nozzle with internal diameter of 0.8 mm into cryogenic surface and forming freezing disk of solution, with drop of volume measuring 7.7 mm diameter ´ 0.139mm height. This technique is called Ultra Rapid Freezing (URF). These frozen drops are then collected for drying in a freeze dryer. By utilizing cryogenic surface instead of atomization into liquid nitrogen, spreads of drop due to the complexity of cryogen evaporation (Leidenfrost effect) are eliminated. Secondly, by employing the URF techniques developed, investigation of the effect of polymer (Polyvinylpyrrolidone) inclusion on the efficiency of this process was conducted. Isoniazid (Iso-Nicotinic Acid Hydrazide) was used as API and distilled water as the solvent. A comparison was also made with a nano-particle produced through URF and lyophilization by using a freeze dryer. Nano particle formation through freeze dryer is depending on freeze-drying cycle which is divided into three steps: freezing (solidification), primary drying (ice sublimation) and secondary drying (desorption of unfrozen water). Through this comparison, the effect of freezing rate on nano formation was observed. Furthermore, Differential Scanning Calorimetry (DSC) was utilized to prevent phase separation with the changing of freezing rate through introduction of heat. The hypothesis of this study is that the rate of freezing is critical in preventing phase separation during freezing, through this way API molecular grow can be inhabited and dispersed with the polymer. Thirdly, to apply the URF technique developed to overcome the low bioavailability limitation, in which enhancement of dissolution rate is targeted. Griseofulvin (GF) was used in the dissolution study. GF is classified as Class II poorly soluble but highly permeable API, according to biopharmaceutical classification system (BCS). In addition to the inclusion of polymer, surfactant (Sodium dodecyl sulphate) was added. DSC is utilized to determine the amorphousity or crystallinity of the product, by observing the melting point. The results demonstrated that URF technique developed offers a highly effective approach to produce nanoparticles, amorphous API and enhancing dissolution rates. Due to increasing freezing rate, phase separation prevention led to control size of crystal formation in nano range. Crystalline API (Isoniazid) yield was higher than 98% particles with size £200 nm were successfully recovered. It can be concluded convincingly, that developed technique is an effective particle formation process for pharmaceutical development (particularly Isoniazid & Griseofulvin) and manufacturing to improve dissolution rates of poorly water soluble APIs.